Crystallization and preliminary X‐ray diffraction analyses of the TIR domains of three TIR–NB–LRR proteins that are involved in disease resistance in Arabidopsis thaliana. Issue 11 (1st November 2013) - Wan, Li; Zhang, Xiaoxiao; Williams, Simon J.; Ve, Thomas; Bernoux, Maud; Sohn, Kee Hoon; Jones, Jonathan D. G.; Dodds, Peter N.; Kobe, Bostjan
Abstract : The Toll/interleukin‐1 receptor (TIR) domain is a protein–protein interaction domain that is found in both animal and plant immune receptors. The N‐terminal TIR domain from the nucleotide‐binding (NB)–leucine‐rich repeat (LRR) class of plant disease‐resistance (R) proteins has been shown to play an important role in defence signalling. Recently, the crystal structure of the TIR domain from flax R protein L6 was determined and this structure, combined with functional studies, demonstrated that TIR‐domain homodimerization is a requirement for function of the R protein L6. To advance the molecular understanding of the function of TIR domains in R‐protein signalling, the protein expression, purification, crystallization and X‐ray diffraction analyses of the TIR domains of the Arabidopsis thaliana R proteins RPS4 (resistance to Pseudomonas syringae 4) and RRS1 (resistance to Ralstonia solanacearum 1) and the resistance‐like protein SNC1 (suppressor of npr1‐1, constitutive 1) are reported here. RPS4 and RRS1 function cooperatively as a dual resistance‐protein system that prevents infection by three distinct pathogens. SNC1 is implicated in resistance pathways in Arabidopsis and is believed to be involved in transcriptional regulation through its interaction with the transcriptional corepressor TPR1 (Topless‐related 1). The TIR domains of all three proteins have successfully been expressed and purified as soluble proteins in Escherichia coli . Plate‐like crystals of the RPS4 TIR domain were obtained using PEG 3350 as a precipitant; they diffracted X‐rays to 2.05 Å resolution, had the symmetry of space group P 1 and analysis of the Matthews coefficient suggested that there were four molecules per asymmetric unit. Tetragonal crystals of the RRS1 TIR domain were obtained using ammonium sulfate as a precipitant; they diffracted X‐rays to 1.75 Å resolution, had the symmetry of space group P 41 21 2 or P 43 21 2 and were most likely to contain one molecule per asymmetric unit. Crystals of the SNC1 TIR domain were obtained using PEG 3350 as a precipitant; they diffracted X‐rays to 2.20 Å resolution and had the symmetry of space group P 41 21 2 or P 43 21 2, with two molecules predicted per asymmetric unit. These results provide a good foundation to advance the molecular and structural understanding of the function of the TIR domain in plant innate immunity.